Japanese Internment of Allied Civilians in the Second World War China: Perspectives on the Enemy Aliens Protection Mechanism. (April 2022) - Yang, Chan
This article discusses the Japanese internment of Allied civilians in occupied China during the Second World War (WWII), with a focus on the period leading up to July 1943, by which point most Allied civilians had entered various internment sites throughout occupied China. This article mainly utilises the archives of the Japanese, the Allied governments and international mediators. The study argues that a provisional international mechanism for protecting enemy aliens was formulated shortly after the outbreak of war. It also finds that although Allied civilians did suffer physically and mentally during Japanese internment in occupied China, at least in the beginning, the Allied governments and the Japanese foreign affairs apparatus, based on this provisional international mechanism and the principle of 'reciprocity', intended to treat them fairly.